When progressing training loads, what are the considerations for healthy and injured athletes? - Gabbett, T.; Sancho, I.; Dingenen, B.; Willy, R. W. (British Journal of Sports Medicine, 2021)
Every sport requires specific physical capacities to enable success and minimise injury risk. For instance, a competitive runner requires adequate muscular force production to counter ground reaction forces for a single step at a given speed (local tissue capacity), and the muscular and cardiovascular endurance to tolerate the accumulation of steps for the time and distance of the event (sport-specific capacity). Failing to adequately develop these physical qualities may result in underperformance and/or increased injury risk. In this editorial we explore how to optimally monitor and progress training loads to improve local tissue and sport-specific capacity. Every sport requires specific physical capacities to enable success and minimise injury risk. For instance, a competitive runner requires adequate muscular force production to counter ground reaction forces for a single step at a given speed (local tissue capacity), and the muscular and cardiovascular endurance to tolerate the accumulation of steps for the time and distance of the event (sport-specific capacity). Failing to adequately develop these physical qualities may result in underperformance and/or increased injury risk. In this editorial we explore how to optimally monitor and progress training loads to improve local tissue and sport-specific capacity....